Immunosuppressive, anti-inflammatory and anti-cancer properties of triptolide: A mini review - Ziaei, Samira (Avicenna J Phytomed, 2016)
OBJECTIVE: Triptolide, the active component of Tripterygium wilfordii Hook F has been used to treat autoimmune and inflammatory conditions for over two hundred years in traditional Chinese medicine. However, the processes through which triptolide exerts immunosuppression and anti-inflammation are not understood well. In this review, we discuss the autoimmune disorders and inflammatory conditions that are currently treated with triptolide. Triptolide also possesses anti-tumorigenic effects. We discuss the toxicity of various triptolide derivatives and offer suggestions to improve its safety. This study also examines the clinical trials that have investigated the efficacy of triptolide. Our aim is to examine the mechanisms that are responsible for the immunosuppressive, anti-inflammatory, and anti-cancer effects of triptolide. MATERIALS AND METHODS: The present review provides a comprehensive summary of the literature with respect to the immunosuppressive, anti-inflammatory, and anti-cancer properties of triptolide. RESULTS: Triptolide possesses immunosuppressive, anti-inflammatory, and anti-cancer effects. CONCLUSION: Triptolide can be used alone or in combination with existing therapeutic modalities as novel treatments for autoimmune disorders, cancers, and for immunosuppression.